Bilateral macular dysplasia ('colobomata') and congenital retinal dystrophy. Issue 9 (September 1985) - Moore, A T; Taylor, D S; Harden, A
Abstract : Three unrelated patients with bilateral macular dysplasia ('colobomata') with no relevant family history were found to have absent or substantially abnormal electroretinograms, implying that there was an associated retinal dystrophy. This may suggest that the macular lesions are associated with a global failure of retinal development, with a regional preponderance rather than a purely localised cause such as an intrauterine infection. It is important to distinguish between congenital infections such as toxoplasmosis and developmental macular colobomata, which have a somewhat similar ophthalmoscopic appearance as a cause of bilateral macular abnormalities seen in young children, since they have different implications for genetic advice and future ophthalmic care.